Potassium Flux and Leaf Movement in Samanea saman : I. Rhythmic Movement - Satter, R. L. (The Rockefeller University Press, 1974)
Samanea leaflets usually open in white light and fold together when darkened, but also open and dose with a circadian rhythm during prolonged darkness. Leaflet movement results from differential changes in the turgor and shape of motor cells on opposite sides of the pulvinus; extensor cells expand during opening and shrink during closure, while flexor cells shrink during opening and expand during closure but change shape more than size. Potassium in both open and closed pulvini is about 0.4 N. Flame photometric and electron microprobe analyses reveal that rhythmic and light-regulated postassium flux is the basis for pulvinar turgor movements. Rhythmic potassium flux during darkness in motor cells in the extensor region involves alternating predominance of inwardly directed ion pumps and leakage outward through diffusion channels, each lasting ca 12 h. White light affects the system by activating outwardly directed K(+) pumps in motor cells in the flexor region.